Cloud computing and services science : Second International Conference, CLOSER 2012, Porto, Portugal, April 18-21, 2012. Revised Selected Papers (Communications in Computer and Information Science,, 2013)
This book constitutes the thoroughly refereed proceedings of the Second International Conference on Cloud Computing and Services Science, CLOSER 2012, held in Porto, Portugal, in April 2012. The 15 papers were selected from 145 submissions and are presented together with one invited paper. The papers cover the following topics: cloud computing fundamentals, services science foundation for cloud computing, cloud computing platforms and applications, and cloud computing enabling technology.